The Effect of Students' Adversity Quotient in the Pandemic Era on Their English Learning Achievement - Sabiq Ariqun Nabih; Nadiah Makmun (ELITE JOURNAL, 2023)
The obstacles and difficulties that students faced in the learning process during the pandemic era, which could have harmed their English learning achievement, inspired this study. This research sought to investigate the efficacy of Adversity Quotient training as a means of improving students' responses and capacities in dealing with issues during the pandemic era, which is likely to have a positive impact on their English learning outcomes. This study used an experimental design and a quantitative method. The cluster sampling technique was used to pick 78 students as participants. They are from the experimental class of XI MIPA 3 and the control class of XI MIPA 2. The experimental class received Adversity Quotient instruction, while the control group did not. Tests (pre-and post-tests), questionnaires, and documentation were utilized to collect data for this study. The hypothetical test was an independent sample t-test. According to the data obtained, the average post-test score in the experimental class was 79.69, while the control class was 76.21. The value of Sig. (2-tailed) in the hypothetical test was 0.022 (Sig. (2-tailed) 0.05). The null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted based on the interpretation. It means that Adversity Quotient training is highly successful in raising students' adversity quotients in order to improve learning outcomes during pandemics. This discovery is likely to assist teachers in improving students' answers and abilities when confronted with issues, which will have a positive impact on their English learning accomplishments during the epidemic period. Keywords: Adversity Quotient, English Learning Achievement, Pandemic Era.